Power and Identity Representation in News on Indonesia’s Capital Relocation: A Fairclough Critical Discourse Analysis - Nurpadillah, Veni; Mardikantoro, Hari Bakti; Mulyaningsih, Indrya; Wilsa, Asrizal Wahdan (SAWERIGADING, 2025)
This study investigates how Metro News and Kumparan.com represent the relocation of Indonesia’s new capital (IKN), focusing on power and identity in media discourse. Using Norman Fairclough’s critical discourse analysis at micro-, meso-, and macrostructural levels, a qualitative approach analyzes online news excerpts and interviews through a matching method validated by triangulation. Findings indicate that Metro News constructs an oppositional identity by critically framing President Jokowi’s policies, reflecting the ideological stance and institutional influence of its ownership. In contrast, Kumparan.com emphasizes government achievements, portraying a progressive and development-oriented identity of the administration. The analysis shows that media discourse functions both as a political watchdog and as a constructor of social and political identities, shaping public perception and legitimizing authority. The study underscores the importance of media literacy, transparency, and public dialogue in fostering critical awareness of strategic national issues such as capital relocation. Further research is recommended to examine how media representations of power and identity affect policy reception and public opinion. AbstrakStudi ini menyelidiki tentang bagaimana Metro News dan Kumparan.com merepresentasikan relokasi Ibu Kota Baru Indonesia (IKN), dengan fokus pada kekuasaan dan identitas dalam wacana media. Menggunakan analisis wacana kritis Norman Fairclough pada tingkat mikro, meso, dan makrostruktural, pendekatan kualitatif menganalisis kutipan berita daring dan wawancara melalui metode pencocokan yang divalidasi oleh triangulasi. Temuan menunjukkan bahwa Metro News membangun identitas oposisional dengan membingkai secara kritis kebijakan Presiden Jokowi, yang mencerminkan sikap ideologis dan pengaruh kelembagaan pemiliknya. Sebaliknya, Kumparan.com menekankan pencapaian pemerintah, menggambarkan identitas pemerintahan yang progresif dan berorientasi pembangunan. Analisis menunjukkan bahwa wacana media berfungsi baik sebagai pengawas politik maupun sebagai konstruktor identitas sosial dan politik, membentuk persepsi publik dan melegitimasi otoritas. Studi ini menggarisbawahi pentingnya literasi media, transparansi, dan dialog publik dalam menumbuhkan kesadaran kritis terhadap isu-isu nasional strategis seperti relokasi ibu kota. Penelitian lebih lanjut disarankan untuk mengkaji bagaimana representasi media tentang kekuasaan dan identitas mempengaruhi penerimaan kebijakan dan opini publik.